Systematic review of infant and young child complementary feeding practices in South Asian families: the India perspective. Issue 4 (23rd November 2017) - Manikam, Logan; Prasad, Ankita; Dharmaratnam, Abina; Moen, Christy; Robinson, Alexandra; Light, Alexander; Ahmed, Sonia; Lingam, Raghu; Lakhanpaul, Monica
Abstract: Objective: Suboptimal nutrition among children remains a problem among South Asian (SA) families. Appropriate complementary feeding (CF) practices can greatly reduce this risk. Thus, we undertook a systematic review of studies assessing CF (timing, dietary diversity, meal frequency and influencing factors) in children aged <2 years in India. Design: Searches between January 2000 and June 2016 in MEDLINE, EMBASE, Global Health, Web of Science, OVID Maternity & Infant Care, CINAHL, Cochrane Library, BanglaJOL, POPLINE and WHO Global Health Library. Eligibility criteria: primary research on CF practices in SA children aged 0–2 years and/or their families. Search terms: 'children', 'feeding' and 'Asians' and derivatives. Two researchers undertook study selection, data extraction and quality appraisal (EPPI-Centre Weight of Evidence). Results: From 45 712 abstracts screened, sixty-four cross-sectional, seven cohort, one qualitative and one case–control studies were included. Despite adopting the WHO Infant and Young Child Feeding guidelines, suboptimal CF practices were found in all studies. In twenty-nine of fifty-nine studies, CF was introduced between 6 and 9 months, with eight studies finding minimum dietary diversity was achieved in 6–33 %, and ten of seventeen studies noting minimum meal frequency in only 25–50 % of the study populations. Influencing factors included cultural influences, poor knowledge on appropriate CF practices and parental educational status. Conclusions: This is the first systematic review to evaluate CF practices in SA in India. Campaigns to change health and nutrition behaviour and revision of nationwide child health nutrition programmes are needed to meet the substantial unmet needs of these children.